Restriction of rights of transfer of securities : does section 8(2)(b)(ii)(bb)of the Companies Act 71 of 2008 create a pactum de non cedendo? - Delport, Petrus Albertus (University of Pretoria, 2019)
Mini Dissertation (LLM)--University of Pretoria, 2018.